Coal Waste, Socioeconomic Change, and Environmental Inequality in Appalachia: Implications for a Just Transition in Coal Country - Greenberg, Pierce (Society & natural resources, 2018)
Resource-dependent communities are subject to both unstable economic patterns and environmental degradation associated with extractive industries. However, few studies have empirically analyzed these dynamics in tandem and over time. This paper explores whether Appalachian neighborhoods closer to coal waste impoundments experienced steeper poverty changes from 1990 to 2000. Impoundment failures have resulted in some of the largest environmental disasters in U.S. history and scientists have expressed concerns over their growing heights and risks. Spatial regression models show that neighborhoods closer to impoundments have higher poverty increases on average, even after controlling for mining employment and other variables. These findings highlight the need for a deeper consideration of the environmental inequalities associated with the continued downturn of coal production and employment in the United States. Further, discussions about just transitions must recognize the legacy hazards and externalities associated with extractive industries - and their impacts on communities.